2022
DOI: 10.18196/pt.v10i1.11428
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Indigenous Mycorrhizae of Corn Plants in Various Soil Types in Gunung Kidul, Indonesia

Abstract: Indigenous Vesicular-Arbuscular Mycorrhizae (VAM) are natural mycorrhizae from specific areas that have good environmental adaptability. This study, conducted from January to November 2020 at the Faculty of Agriculture, Universitas Gadjah Mada,  aimed to isolate the vesicular-arbuscular mycorrhizal fungus so that it can be used as information on the type and role of VAM on Gunung Kidul soil. The research was arranged in a Completely Randomized Design (CRD) with three factors. The first factor was soil type fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Yao et al (2008) discovered differential colonisation in the roots of Cyperus difformis by native AMF, which is low, but appears to be associated with numerous vesicles. In contrast Diannastiti et al (2022) that stated indigenous AMF was able to colonise corn roots by more than 89%.…”
Section: Am Fungal Colonisationmentioning
confidence: 78%
See 1 more Smart Citation
“…Yao et al (2008) discovered differential colonisation in the roots of Cyperus difformis by native AMF, which is low, but appears to be associated with numerous vesicles. In contrast Diannastiti et al (2022) that stated indigenous AMF was able to colonise corn roots by more than 89%.…”
Section: Am Fungal Colonisationmentioning
confidence: 78%
“…Our results showed that there was the colonisation of sorghum roots without AMF inoculation because unsterilised media were used. According to Diannastiti et al (2022), there is no elimination of AMF in unsterilised soil, so indigenous AMF can still colonise the roots. Thus, the plants that had not been inoculated with AMF were colonised by indigenous AMF in the present study (Figure 1).…”
Section: Am Fungal Colonisationmentioning
confidence: 99%